Climate services for protection against wheat blast in Bangladesh - CGIAR Research Program on Wheat (2019)
Wheat blast advisories can be used by farmers to protect wheat crops from blast disease that can cause up to 30% yield losses. Other climate information services are under quantification for economic benefits at this time. An early warning system for wheat blast can be found at: http://34.80.72.205/.